Transumbilical single-incision laparoscopic inguinal hernia repair – feasibility study on anatomical specimens - Andreas Kirschniak; Thomas Shiozawa; Markus Küper; Frank A. Granderath (Videosurgery and Other Miniinvasive Techniques)
Laparoscopic inguinal hernia has replaced open surgery in recent years. For transabdominal preperitoneal mesh placement,3 incisions have to be made to prepare the inguinal region, place the mesh and adapt the peritoneum witha suture. We describe the feasibility of a single incision transumbilical hernia repair. For this, we operated on3 anatomical specimens (2 male, 1 female), which had been conserved using alcohol-glycerol fixation. A subumbilical1.5 cm incision was performed, and three 5 mm trocars were inserted. The preparation and procedure steps conformedto conventional laparoscopic transabdominal preperitoneal hernia repair (TAPP). In the right port we used a 5 mm30 degree laparoscope, for preparation a grasper and scissors with optional flexure. Mean procedure time was 45.5 min(35-55 min, ±7 min). The left and right inguinal region was prepared. Adaptation in handling and ergonomics needsfamiliarization.